1992
DOI: 10.1002/jbm.820260111
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis of the push‐out test: Influence of test conditions

Abstract: The commonly used method for quantitative evaluation of the strength of a boneimplant interface is the push-out test. In order to give an impulse to standardization and t o g a i n more insight in t h e biomechanics of the push-out test, a finite element analysis of this test was performed. This study focused on the influence of test conditions on the push-out results. The influence of the following four parameters on the interface stress distribution was tested: (a) clearance of the hole in the support jig, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 11 publications
1
107
0
2
Order By: Relevance
“…The specimens were placed on a metal support jig with a 9.4-mm diameter central opening. Centering the implant over the opening assured a 0.7-mm distance between the implant and support jig as recommended by Dhert et al 17 Implants were pushed outsidein of the bone. A preload of 2 N defined the start of the test.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…The specimens were placed on a metal support jig with a 9.4-mm diameter central opening. Centering the implant over the opening assured a 0.7-mm distance between the implant and support jig as recommended by Dhert et al 17 Implants were pushed outsidein of the bone. A preload of 2 N defined the start of the test.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…It is accepted that such tests are able to estimate the mechanical interlocking between bone and implant 21 . The results of push-out tests demonstrated that a considerably high force was required to disrupt the boneimplant interface, and that it was increasingly higher as the period elapsed between surgery and sacrifice grew, reaching values around 100N.…”
Section: Discussionmentioning
confidence: 99%
“…2). This plate (with co‐located 25.4 mm spaced Ø16 mm holes) spread the clamping load over the entire surface of the sawbones testing block while providing sufficient hole clearance (always >2 mm) to prevent clamping stress from interfering with the test 41. A low friction bearing table allowed for unrestricted translation in the horizontal plane during all tests.…”
Section: Methodsmentioning
confidence: 99%